Perception of peace among pre-service teachers - Tuğba Selanik Ay; Abdullah Gokdemir (Institute of Advanced Engineering and Science, 2020)
This research was carried out to determine pre-service teachers' perceptions of “peace”. This was a qualitative research based on case studies scenarios and document analysis. The sample of the study consists of 180 teacher-candidates studies in the social sciences and primary education at a state university in the Aegean Region of Turkey. These Preservice teachers were given scenarios and asked to retain the five scenarios given to them. In this context, in the study, of the document types personal documents and peace-related sample case scenarios retained by teacher candidates themselves were used. The scenarios gathered are examined as a document and subjected to content analysis, and the data obtained are presented in tables and supported with direct quotations. As a result of the findings obtained from sample case study scenarios, themes of peace were obtained in the context of the teaching profession, in daily life, in the national and universal context. In the context of teacher behaviors and methods and techniques that can be used to bring peace value, teacher candidates’ state creating a democratic classroom climate, enabling free discussion of ideas and encouraging children to empathize. In addition,pre-service teachers stressed the importance of being a role-model and encouraging students to empathize under the theme of teacher behaviors supporting the value of peace.